ADSORPTION BEHAVIOUR OF CADMIUM-(II) ON HYDROUS OXIDE INORGANIC RESINS - Sunarhadijoso Soenarjo; Chandra Wijaya (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2006)
ADSORPTION BEHAVIOUR OF CADMlUM-(II) ON HYDROUS OXIDE INORGANIC RESINS. Hydrous titanium oxide (HTO), hydrous zirconium oxide (HZO) and hydrous cerium oxide (HCO) resins were subjected to batch experiments on cadmium-(ll) adsorption studies using standard solutions of Cd-(ll)-nitrate. This was aimed to gain more experimental data in concern to choose inorganic resin for separation of Cd2+ - In3+. matrices in production technology of indium radioisotopes (111/115mln) as well as for recovery of high-enriched cadmium-(112/114Cd) target. Series of cold Cd-(ll)-nitrate standard solutions prepared from natural cadmium were treated by means of mixing and stirring with the resins at room temperature and then separated from the resin by centrifugation. The separating supernatants were then spectrophotometrically analyzed for Cd-(ll) determination as compared to Cd-(ll) content in the corresponding initial solutions. The results indicate that there was no Cd(ll) adsorption on Merck-produced titanium oxide pre-treated with neutral, acidic or basic condition. The Cd-(ll) adsorption occured either on zirconium oxide or on cerium oxide. The self-synthesized HCO having molecule formula of CeO2.nH2O (n = 0.8868 ± 0.0026) showed higher Cd-(ll)-adsorption capacity than self-synthesized HZO that was found to have molecule formula of ZrO2=.qH2O (q = 1.7613 ± 0.0836), i.e. (47.167 ± 0.083) x 10-3 mg/mg as compared to (12.200 ± 0.255) × 10-3 mg/mg. The ready-used zirconium oxide produced by Atomergic Chem. Corp. showed significantly smaller, i.e. (9.449 + 0.092) x 10-3 mg/mg. The influence of hydrate content in the resins to the Cd(ll)-adsorption capacity was observed by comparing Cd-(ll)-adsorption capacity of HCO heated up to 400°C (found as CeO2.0.1706H2O) and that of HCO heated up to 800°C (found as CeO2.0.0400H2O), i.e. (116.567 ± 0.839) x 10-3 mg/mg and (146.533 ± 0.897) x 10-3 mg/mg respectively.